2021
DOI: 10.1080/14631369.2021.1882289
|View full text |Cite
|
Sign up to set email alerts
|

The myth of academic tolerance: the stigmatisation of East Asian students in Western higher education

Abstract: This article focuses on the stigmatisation of East Asian students within Western universities. This is necessary because East Asian students are often overlooked in existing literature about racism in Western academia. It is argued that East Asian students may be generalised as undesirable students in ways that resonate with more broadly held prejudices about East Asian people. To illustrate this, academic publications about East Asian students are critiqued. This involves identifying, analysing and deconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 57 publications
0
22
0
3
Order By: Relevance
“…Thus, on numerous occasions, I have witnessed certain white academics in East Asia: (a) treating East Asian academics as invisible in academic discussions, (b) excluding East Asian academics from social activities, (c) making no effort to familiarise themselves with East Asian colleagues' research agendas and (d) dismissing East Asian academics' scholarship; all of which correspond with studies which have found that white academics in Western universities may hold condescending views about the worth of academics of colour (Arday 2018: 147-148;Grant 2019: 130;Mohamed and Beagan 2019: 339-340). Similarly, I have observed some white academics in East Asia: (a) showing a diminished level of commitment to the education of East Asian students, (b) refusing to adapt their teaching to the East Asian context, (c) dismissing East Asian students' feedback as unimportant and (d) partaking in the same type of patronising stereotyping of East Asian students that I have previously identified in Western academia (Moosavi 2020;Moosavi 2021). Notably, East Asian academics and East Asian students may be cognisant of such belittling and discriminatory treatment, as was confirmed to me on two separate occasions when East Asian students and an East Asian academic confided in me that they felt dehumanised by the way in which certain white academics routinely treated them.…”
Section: Sustaining White Privilegementioning
confidence: 70%
See 2 more Smart Citations
“…Thus, on numerous occasions, I have witnessed certain white academics in East Asia: (a) treating East Asian academics as invisible in academic discussions, (b) excluding East Asian academics from social activities, (c) making no effort to familiarise themselves with East Asian colleagues' research agendas and (d) dismissing East Asian academics' scholarship; all of which correspond with studies which have found that white academics in Western universities may hold condescending views about the worth of academics of colour (Arday 2018: 147-148;Grant 2019: 130;Mohamed and Beagan 2019: 339-340). Similarly, I have observed some white academics in East Asia: (a) showing a diminished level of commitment to the education of East Asian students, (b) refusing to adapt their teaching to the East Asian context, (c) dismissing East Asian students' feedback as unimportant and (d) partaking in the same type of patronising stereotyping of East Asian students that I have previously identified in Western academia (Moosavi 2020;Moosavi 2021). Notably, East Asian academics and East Asian students may be cognisant of such belittling and discriminatory treatment, as was confirmed to me on two separate occasions when East Asian students and an East Asian academic confided in me that they felt dehumanised by the way in which certain white academics routinely treated them.…”
Section: Sustaining White Privilegementioning
confidence: 70%
“…In this regard, future third wave Critical Whiteness Studies research must coalesce with other cutting-edge scholarship on race and ethnicity in East Asia which has deliberately sought to go beyond whiteness, such as that which examines the racial fault lines that underpin a number of political and violent conflicts in the region (Barr andSkrbiš 2011 [2008]; Mukherjee 2021), or that which explores the complexities of mixed-race East Asians (Rocha and Fozdar 2017;Rocha and Yeoh 2021), or that which focuses on the ways that East Asians may hold racist views toward those that they share the same race with (Ang and Colic-Peisker 2021;Ho and Kathiravelu 2021;Hough 2021;Ortiga 2015). While it may be tempting to subscribe to 'the myth of academic tolerance' that suggests that universities are especially inclusive spaces (Moosavi 2021), this article has sought to draw attention to the intricacies of whiteness and white privilege in East Asian higher education with the hope that it may provoke us to now ask what we do about the racial hierarchies that often exist within East Asian universities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article also considers data relating to Athena Swan, an initiative which has existed for more than 15 years and which is designed to promote gender equality in UK higher education. The data used for this article was taken from the relevant websites of the three initiatives 3 . The comparison that is made is possible because all three initiatives have a similar approach of awarding gold, silver and bronze awards to universities that are able to demonstrate a particular commitment to the respective causes.…”
Section: Methodsmentioning
confidence: 99%
“…There is a well-established body of academic literature that draws attention to the racism that people of colour 1 encounter in UK universities [1][2][3]. This racism often results in people of colour feeling that UK university campuses are hostile spaces that generate a variety of uncomfortable experiences for students and staff.…”
Section: Introductionmentioning
confidence: 99%